Three new species of Ophiotaenia La Rue, 1911 (Cestoda: Proteocephalidae) from dipsadine snakes (Squamata: Colubridae) in Ecuador - de Chambrier, Alain; Kuchta, Roman; Scholz, Tomas (Folia parasitologica, 2024)
The parasite fauna of Neotropical reptiles is poorly known, and the number of parasites described in these hosts does not seem to correspond to the actual species diversity in this zoogeographical region. This also applies to tapeworms such as proteocephalids, which are rarely found in reptiles and are strictly specific to their reptilian hosts. In the present paper, three new species of Ophiotaenia La Rue, 1911 are described from three dipsadine snake species (Squamata: Colubridae) in Ecuador, namely O. jeanmarctouzeti sp. n. from the Neotropical blunt-headed treesnake Imantodes cenchoa (Linnaeus), O. barraganae sp. n. from the beautiful calico snake Oxyrhopus formosus (Wied-Neuwied) and O. velascoae sp. n. from the forest flame snake Oxyrhopus petolarius (Linnaeus). The new species are characterised by type 1 uterine development, the number and distribution of testes, the size of the scolex and other metric features. As no molecular data are available on the specimens collected more than 35 years ago, the phylogenetic relationships of the individual taxa are not known.
Keywords: Dipsadinae; Ophidia; Ecuador; Colubridae; morphology; Tapeworms; mužské pohlaví; cestodózy; South America; species diversity; taxonomy; Ekvádor; ženské pohlaví; zvířata; fylogeneze; Species Specificity; Cestoda; druhová specificita; Cestode Infections; Female; Phylogeny; Male; Animals